Multipla osebnost: prikaz primera - Židanik, Miloš (Zdravniški vestnik, 2004)
Background. Multiple personality disorder is characterised by splited individual ego-states and splited professional community arguing whether this disorder actually exists or not. Methods. In this case report study a supportive psychodynamic psychotherapy of a patient with multiple personality disorder is presented, that lasted for 4.5 years and resulted in ego-reintegration. Conclusions. The spliting between different ego-states is powered by unneutralised aggression with the possibility of hetero- and autoaggressive behaviour. Therefore the patient in the analytically orientedpsychotherapeuticprocess is athigh risk and a safe therapeutic (e. g. in patient) setting has to be provided.
Keywords: Adult; Antipsihotiki; Antipsychotic Agents; Avtodestruktivno vedenje; Disociacijske motnje; Dissociative Disorders; Drug Therapy; Multiple-Personality Disorder; Odrasli; Psihoterapija; Psychotherapy; Self-Injurious Behavior; Therapy